Wind-induced vibration mitigation of video screen rooms in high-rise buildings. (October 2021) - Rizzo, Fabio; Ierimonti, Laura; Venanzi, Ilaria; Sacconi, Stefano
Abstract: Video walls, made of closely spaced video screen systems, are currently very used in architecture and interior design applications. To have a continuous image, the gaps between the screens must be limited as much as possible and the vibration of the supporting structure must be reduced to avoid ponding and consequent screens damage. The problem is particularly important when video walls are in rooms inside high-rise buildings that, due to their high deformability, experience significant wind-induced drifts and accelerations. In this case, it is convenient to mount video screens on a three-dimensional lightweight frame substructure (video wall room), supported by the building's floor. To ensure the limitation of the relative displacements between the screens in case of strong winds, the substructure can be equipped with base isolators capable of mitigating the global response when the buildings' induced accelerations overcome specific thresholds. This paper is aimed at investigating the wind-induced response of video screen rooms located inside wind-excited high-rise buildings and at providing guidance for the design of the base isolation devices. The floors' accelerations measured during aeroelastic wind tunnel tests on a high-rise building are applied as base accelerations to a finite element method model of the video room. The parameters of the constitutive behavior of the base isolation system are optimally calibrated as a function of the wind speed and position over the building height.